Determinación de los factores de contaminación del agua de consumo de la Comunidad Llangos el Carmen, Parroquia San Andrés - Castillo Jaramillo, Luciana Paulina (2024)
This investigation aimed to determine the contamination factors of drinking water in the Llangos El Carmen community, San Andrés parish. The methodology involved applied research with a field and laboratory design, collecting primary and secondary information. Surveys were carried out on 55 people to learn about the biophysical and socioeconomic conditions of the study area, along with a physicochemical and microbiological analysis that allowed for the evaluation of the quality of the water in the reservoir and the distribution network. The socioeconomic survey verified that the water collection and distribution systems are in good condition. However, some users were dissatisfied with the service quality, which indicates the need to improve drinking water control techniques. Regarding physicochemical parameters such as pH, conductivity, turbidity, sulfates, alkalinity, sulfates, nitrates, phosphates, hardness, TDS, and coliforms, they are within the normal range established by TULSMA and INEN. The BOD5 exceeds the value established by the TULSMA regulations since they exceed the maximum limit of 2 in both the branches and the Tank during weeks 1 and 3. except for the BOD, which exceeded the maximum limit on certain occasions. A cleaning and disinfection program was proposed, as well as distribution and training measures to guarantee adequate consumption and contribute to the health of the inhabitants. Considering this data to design solutions adapted to the community's needs and ensure a safe and reliable drinking water supply for all its residents is essential.